Peserta Magang dan Keadilan Hukum Guna Mengupas Perlindungan dalam Praktik Kerja - Andana Kanz, Athar Tristan; Sakti, Reza Yudha; Tambunan, Yudha Yosephin; Sinaga, Aditia; Arya Wibowo, Savero Pramudika (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Interns are a key element in the transition from education to work. However, their position is often at an unclear crossroads in terms of legal status and protection. Many interns face unfair treatment, such as excessive working hours, tasks that are not in line with training objectives, and minimal compensation or access to basic rights such as social security. This study aims to examine aspects of legal justice for interns, evaluate existing policies, and provide recommendations for better legal protection. The methodology used includes normative legal analysis and an empirical approach to internship work practices in various sectors. The results of the study show that there is a mismatch between formal regulations related to internships and their implementation in the field. Some countries or regions have weak legal frameworks, while in other regions, violations against interns still often occur despite adequate regulations. This is exacerbated by the lack of supervision and law enforcement against companies or institutions that exploit interns. This study highlights the importance of strengthening policies through an integrated approach, including the preparation of clear work contracts, determining the rights and obligations of both parties, and providing an effective complaint mechanism for interns. In addition, synergy is needed between the government, educational institutions, and the private sector to create an internship system that is not only beneficial to companies, but also protects interns as potential future workers. Thus, the implementation of the principle of legal justice in internship work practices can be the foundation for the development of an inclusive and sustainable world of work